“Moistening Things Silently”: Reflections on Christian Education and the Sinicization of Christianity - LIN Chaoqun, (Journal of Research for Christianity in China (JRCC), 2025)
Christian education encompasses both Christianity and education. Exploring Christian education involves analyzing it from a Christian perspective, tracing its historical development through the Bible, and applying it to contemporary education as a starting point. This process involves organizing and applying insights to encourage more Christians to focus on Christian education, allowing this subject to permeate various fields and lay a solid foundation for the Lord's work. This historical mission of education is subtly embodied in the Old Testament's unique educational model and Jesus' representative teachings in the New Testament. Both consistently demonstrate an indisputable truth: the critical importance of the educational environment, the vital role of the teacher's example, and the vital unity of spiritual formation and practical application. These essential truths require nurturing like gentle rain nourishing the earth—through love, patience, wisdom, and truth—to cultivate life's gradual growth. Moreover, this profound educational responsibility demands greater attention, cultivation, and implementation today. This is precisely where the purpose and value of Christian education lie.